Association of common genetic variants with chronic axonal polyneuropathy in the general population: a genome-wide association study - Taams, Noor E.; Knol, Maria J.; Hanewinckel, Rens; Drenthen, Judith; Reilly, Mary M.; van Doorn, Pieter A.; Adams, Hieab H. H.; Ikram, M. Arfan (Frontiers in Neurology, 2024)
Introduction Disease susceptibility of chronic axonal polyneuropathy is not fully explained by clinical risk factors. Therefore, we determined the contribution of common genetic variants in chronic axonal polyneuropathy in the general population. Methods This study was performed in two population-based studies. Polyneuropathy diagnosis was based on screening in the Rotterdam Study and on ICD-10 codes in the UK Biobank. We determined the heritability of the sural nerve amplitude and performed genome-wide association studies of chronic axonal polyneuropathy and sural sensory nerve amplitude. Furthermore, we zoomed in on variants in and surrounding 100 autosomal genes known to cause polyneuropathy based on literature and expert knowledge (candidate genes), and we performed a gene-based analysis. Analyses were adjusted for age, sex and population stratification. Results Chronic axonal polyneuropathy was present in 2,357 of the 458,567 participants and 54.3% of the total population was female. Heritability of sural nerve amplitude was 0.49 (p = 0.067) (N = 1,153). No variants (p < 5.0×10−8) or genes (p < 2.7×10−6) reached genome-wide significance for its association with polyneuropathy. Focusing on variants in and surrounding the candidate genes in the GWAS (p < 3.9×10−6) and on these genes in the gene-based analysis (p < 5.0×10−4) neither yielded significant results. Discussion We did not find common variants associated with chronic axonal polyneuropathy in the general population. Larger studies are needed to determine if genetic susceptibility based on both common and rare genetic variants affect the risk for chronic axonal polyneuropathy in the general population.